The Government’s Internal Control System in Realizing Good Governance at the Regional Financial Agency of Pontianak City - Wanda Michelia Oktafiani; Khristina Yunita; Haryono Haryono; Rusliyawati Rusliyawati; Juanda Astarani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the role of the Government Internal Control System (SPIP) in supporting the implementation of good governance principles at the Pontianak City Regional Financial Agency. The approach used is descriptive qualitative, with inscription collection techniques through interviews, documentation studies, and literature reviews. SPIP is a control system that is carried out comprehensively and continuously by all elements in a government organization, intending to provide adequate assurance of achieving operational effectiveness, reliability of financial reporting, security of state assets, and compliance with laws and regulations. The results of the study indicate that the implementation of SPIP at the Pontianak City Regional Financial Agency refers to Government Regulation 60 of 2008, which consists of five main components: control environment, risk assessment, control activities, information and communication, and monitoring. The five components have been implemented quite well and have contributed to increasing transparency, accountability, and organizational governance effectiveness. However, there are still challenges in its implementation, such as unequal understanding among employees regarding the concept and function of SPIP, and the need to strengthen the role of the Government Internal Supervisory Apparatus (APIP) in supervisory activities. Overall, SPIP has a strategic role in encouraging the realization of good governance within the Pontianak City Regional Finance Agency.